Starvation Alters Gut Microbiome in Black Soldier Fly (Diptera: Stratiomyidae) Larvae - Yang, Fengchun; Tomberlin, Jeffery K.; Jordan, Heather R. (Frontiers in Microbiology, 2021)
The impact of starvation on host gut microbiomes is poorly understood. Deciphering shifts in metabolically active associated bacterial communities could lead to discoveries of mechanisms regulating the sensation of hunger. We used black soldier fly (BSF) larvae as a model to explore this relationship due to foundational information of bacteria interactions with this species having already been documented. Bacteria associated with food substrates of BSF impact corresponding larval life-history traits (e.g., larval development); however, it is not known if the state (i.e., starved) BSF larval host state impacts the gut microbiome is not known. In this study, we measured microbial community structural and functional shifts due to BSF larvae starvation. At the phylum level, community diversity decreased significantly during BSF larval starvation (P = 0.0025). Genus level DESeq2 analysis identified five genera with significantly different relative abundance (q < 0.05) across the 24 and 48 H post initiation of starvation: Actinomyces, Microbacterium, Enterococcus, Sphingobacterium, and Leucobacter. Finally, we inferred functional potential and significantly predicted functional KEGG Orghology (KO) abundance. We demonstrated the associated metabolically active microbial community structure and function could be influenced by host feeding status. Such perturbations, even when short in duration (e.g., 24 H) could stunt larval growth and waste conversion due to lacking a full complement of bacteria and associated functions.